2016
DOI: 10.1159/000448758
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine, Interleukin-6 and Tumor Necrosis Factor Alpha Plasma Levels during Intermittent Epidural and Continuous Wound Infusion of Ropivacaine for Analgesia after Hysterectomy or Myomectomy: An Observational Study

Abstract: Background/Aims: The concentration-time profile of the long-acting local anesthetic ropivacaine after epidural (EP) administration at fixed time intervals or continuous subcutaneous (SC) infusion has not been fully evaluated. The objective of this work was to determine total plasma concentrations of ropivacaine and changes in cytokine interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) levels during EP and SC. Methods: In this prospective randomized controlled trial, 18 patients undergoing abdominal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The current study reported that at 2-h postpartum VAS score of parturient women of the DR2 cohort was fewer than those of parturient women of the SR1 and the SR2 cohorts and statistically the same as those of parturient women of the DR1 cohort. The results of the VAS score of the current study were in concordance with those of randomized trials [2,[16][17][18]. Dexmedetomidine reduces the release of norepinephrine by activating the presynaptic α2-receptor and inhibits the release of pain signals by stimulating the postsynaptic α2-receptor [19].…”
Section: Discussionsupporting
confidence: 87%
“…The current study reported that at 2-h postpartum VAS score of parturient women of the DR2 cohort was fewer than those of parturient women of the SR1 and the SR2 cohorts and statistically the same as those of parturient women of the DR1 cohort. The results of the VAS score of the current study were in concordance with those of randomized trials [2,[16][17][18]. Dexmedetomidine reduces the release of norepinephrine by activating the presynaptic α2-receptor and inhibits the release of pain signals by stimulating the postsynaptic α2-receptor [19].…”
Section: Discussionsupporting
confidence: 87%
“…With regard to the specific concentration of ropivacaine in labor analgesia, Zhi reported that high‐dose ropivacaine was prone to block the motor nerves of the uterus to weaken uterine contractions, thereby affecting the normal labor process . Markantonis et al . also found that the use of the lowest concentration of ropivacaine that could achieve desirable analgesic effect could reduce the motor block of uterus and also promote patient's comfort.…”
Section: Discussionmentioning
confidence: 99%